Calculus Solutions Ex#1.2

Loader Loading...
EAD Logo Taking too long?

Reload Reload document
| Open Open in new tab
Q.01
Solution:
Given that

    \[\lim_{x \rightarrow a} f(x)=2,\]

    \[\lim_{x \rightarrow a} g(x)=-4\]

    \[\lim_{x \rightarrow a} h(x)=0.\]


(a)

    \[\begin{aligned} \lim_{x \rightarrow a}[f(x)+2 g(x)] & =\lim_{x \rightarrow a} f(x)+2 \underset{x \rightarrow a}{\operatorname{lim}} g(x) \\ & =2+2(-4)=2-8=-6 \end{aligned}\]


(b)

    \[\begin{aligned} \lim _{x \rightarrow a}[h(x)-3 g(x)+1] & =\lim_{x \rightarrow a} h(x)-3 \underset{x \rightarrow a}{\operatorname{lim}} g(x)+\underset{x \rightarrow a}{\operatorname{lim}}(1) \\ & =0-3(-4)+1=13 \end{aligned}\]


(c)

    \[\lim_{x \rightarrow a}[f(x) g(x)]=\left(\lim _{x \rightarrow a} f(x)\right)\left(\lim_{x \rightarrow a} g(x)\right)\]

    \[=(2)(-4)=-8\]


(d)

    \[\lim_{x \rightarrow a}[g(x)]^2 \Rightarrow\left[\lim_{x \rightarrow a} g(x)\right]^2=[-4]^2=16\]


(e)

    \[\begin{aligned} \lim_{x \rightarrow a} \sqrt[3]{6+f(x)} & =\sqrt[3]{{\lim}_{x \rightarrow a}(6)+\lim_{x \rightarrow a} f(x)} \\ & =\sqrt[3]{6+2}=\sqrt[3]{8}=\left(2^3\right)^{1 / 3}=2 \end{aligned}\]


(f)

    \[\lim _{x \rightarrow a} \frac{2}{g(x)}=\frac{2}{\lim_{x \rightarrow a} g(x)}=\frac{2}{-4}=-1 / 2\]

Q.02
Solution:
First of all, we shall find the following limits.

    \[\lim_{x \rightarrow 0} f(x), \quad \lim_{x \rightarrow 2} f(x), \quad \lim_{x \rightarrow 0} g(x), \quad  \lim_{x \rightarrow 2} g(x).\]

 
(i) Limit of f(x) at x=0.
\lim_{x \rightarrow 0^{-}} f(x)=1
This is because as x approaches 0 from left side, f(x) approaches 1.

\lim_{x \rightarrow 0^{+}} f(x)=-2
The reason is as x approaches 0 from the right side, f(x) approaches -2.

Since \lim_{x \rightarrow 0^{-}} f(x) \neq \lim_{x \rightarrow 0^{+}} f(x).
Therefore \lim_{x \rightarrow 0} f(x)does not exist.

(ii) Limit of f(x) at x=2

\lim_{x \rightarrow 2^{-}} f(x)=0

We see from the figure given in the book that as x \rightarrow 2  from left side, f(x) approaches 0.

\lim_{x \rightarrow 2^{+}} f(x)=0

because as x \rightarrow 2  from the right side, f(x) approaches 0.
Since \lim_{x \rightarrow 2^{-}} f(x) =0= \lim_{x \rightarrow 2^{+}} f(x).
Therefore \lim_{x \rightarrow 2} f(x)=0.

(iii) Limit of g(x) at x=2

\lim_{x \rightarrow 2^{-}} g(x)=0

We see from the figure given in the book that as x \rightarrow 2  from left side, g(x) approaches 0.

\lim_{x \rightarrow 2^{+}} g(x)=0
because as x \rightarrow 2  from the right side, f(x) approaches 0.
Since \lim_{x \rightarrow 2^{-}} g(x) =0= \lim_{x \rightarrow 2^{+}} g(x).
Therefore \lim_{x \rightarrow 2} g(x)=0.
(iv) Limit of g(x) at x=0

\lim_{x \rightarrow 0^{-}} g(x)=2, \quad \quad \lim_{x \rightarrow 0^{+}} g(x)=2.
As \quad \lim_{x \rightarrow 0^{-}} g(x)=2=\lim_{x \rightarrow 0^{+}} g(x)

    \[\therefore \quad \lim _{x \rightarrow 0} g(x)=2\]


(a)

    \[\lim_{x \rightarrow 2}[f(x)+g(x)]=\lim_{x \rightarrow 2} f(x)+\underset{x \rightarrow 2}{\operatorname{lim}} g(x)=0+0=0\]


(b)

    \[\lim_{x \rightarrow 0}[f(x)+g(x)]=\lim_{x \rightarrow 0} f(x)+\lim_{x \rightarrow 0} g(x)\]

limit does not exist because \lim_{x \rightarrow 0} f(x) does not exist.

(c)

    \[\begin{aligned} \lim_{x \rightarrow 0^{+}}[f(x)+g(x)] & =\lim_{x \rightarrow 0^{+}} f(x)+\lim_{x \rightarrow 0^{+}} g(x) \\ & =-2+2=0 \end{aligned}\]


(d)

    \[\begin{aligned} \lim_{x \rightarrow 0^{-}}[f(x)+g(x)] & =\lim_{x \rightarrow 0^{-}} f(x)+\lim_{x \rightarrow 0^{-}} g(x) \\ \\ & =1+2=3 \end{aligned}\]